Adventures with Natural Wonders - Kwek, Karen (Singapore : WS Education, an imprint of World Scientific Publishing Co. Pte. Ltd., 2022)
Adventures with Natural Wonders is an immersive encounter with more than 20 natural phenomena that deserve special mention. Which is the world's largest living feline? Where are the most impressive waterfalls on Earth? What makes the oceans glow in the dark? Climb to the summit of Mount Kilimanjaro. Follow the trail of a mythical Irish giant. And glide over Cappadocia in a hot-air balloon. From animal oddities to weird weather effects, and tiny grains of sand to towering geographical landforms, experience the breathtaking natural world as never before!
Keywords: Natural history -- Comic books, strips, etc; Natural history -- Juvenile literature; Natural areas -- Comic books, strips, etc; Natural areas -- Behavior -- Juvenile literature; Graphic novels; Comic books, strips, etc